Investimentos Públicos em infraestrutura no Brasil: uma análise a partir de um modelo DSGE - Alves, Karlos Rafael Soares (2025)
The objective of this study is to analyze the macroeconomic impacts of delays inherent to the implementation of public investments in Brazil. For this purpose, a Dynamic Stochastic General Equilibrium (DSGE) model is used, with simulations conducted to evaluate the impacts of expansionary shocks in public consumption and investment. The research considers the effects of delays, such as time to spend and time to build, on the effectiveness of fiscal policies. The model is based on the New-Keynesian theory, inspired by the framework proposed by Ramey (2020), incorporating relevant specifications for the Brazilian economy, such as habit formation in consumption, liquidity constraints, investment adjustment costs, and variable capital utilization. Impulse Response Functions (IRFs) and fiscal multipliers are employed as the main metrics to measure short- and long- term effects. The results indicate that delays in public investment execution significantly reduce the fiscal stimulus effects on output, with smaller or even negative impacts in the short term. Public consumption demonstrates a greater capacity to generate short-term stimulus compared to public investment under delay scenarios.